Selection and Modelling of a New Single-Domain Intrabody Against TDP-43 - Gilodi, Martina; Lisi, Simonetta; F. Dudás, Erika; Fantini, Marco; Puglisi, Rita; Louka, Alexandra; Marcatili, Paolo; Cattaneo, Antonino; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2022)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder associated to deteriorating motor and cognitive functions, and short survival. The disease is caused by neuronal death which results in progressive muscle wasting and weakness, ultimately leading to lethal respiratory failure. The misbehaviour of a specific protein, TDP-43, which aggregates and becomes toxic in ALS patients’ neurons, is supposed to be one of the causes. TDP-43 is a DNA/RNA-binding protein involved in several functions related to nucleic acid metabolism. Sequestration of TDP-43 aggregates is a possible therapeutic strategy that could alleviate or block pathology. Here, we describe the selection and characterization of a new intracellular antibody (intrabody) against TDP-43 from a llama nanobody library. The structure of the selected intrabody was predicted in silico and the model was used to suggest mutations that enabled its experimental validation. We showed how coupling experimental methodologies with in silico design may allow us to obtain an antibody able to recognize the RNA binding regions of TDP-43. Our findings represent a strategy for the mitigation of TDP-43 proteinopathy in ALS and provide a potential new tool for diagnostics.